TINJAUAN SEMIOTIKA ATAS PEMAHAMAN HADITH DALAM KITAB FATH ALBARI KARYA IBN HAJAR AL-ASQALANI - Benny Afwadzi (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2020)
This article aims to analyze semiotically on the Muslim scholars' understanding of the hadith in Fath Albari, written by Ibn Hajar Al-Asqalani. Focus of the study refers to three things; understanding models, examining semiotically (significance and communication) on understanding models, and contribution of semiotics in the hadith understanding discourse. By making two hadiths as its analysis objects; first, the hadith about believers who eat with one intestine and infidels with seven intestines; second, the hadith regarding the deeds most loved by Allah SWT. The results of the study show that the understanding model of hadith in Fath Albari is divided into textual (symbolic and non-symbolic) and contextual (symbolic and non-symbolic) models of understanding. This model, semiotically (significance and communication) has given a new nuance in the study of hadith understanding. The understanding model of the first hadith, in semiotic significance, indicates the existence of an understanding model with a signifier of denotation and connotation levels. In semiotic communication, the understanding model of the second hadith is seen more systematic because it elaborates reasoning continuously, and shows the important contribution of semiotics in the hadith understanding discourse, like eliminating truth claims and being media of developing textual and contextual understanding.